North Sumatera Convention Center - Andalucia .; Marini . (International Journal of Architecture and Urbanism, 2018)
Sumatera Utara has enhancement of population growth around 2.33% per year and economic growth around 14.7% per year. By all means, this data effect on trade sector, industry sector, entertainment sector, and education sector. From the data above can be obtained that Medan needs supporting facilities to organizing even such as conference, exhibition, a party even, or concert which nationally or internationally. There are a few even for entertainment and art in Medan seen from rarely held music or art performance nationally or internationally. Moreover, there is a very few venue to hold it. North Sumatra Convention Center is built at Jl. H. Adam Malik. This location is chosen because it is by the District of West Medan, which is destined for commercial building supporting the economy. The theme of the design is Contemporary Architecture. This theme is the result of the author's thought to make this building also become Landmark Medan. With the design of the new Convention Center in Medan itself aims to create a place for conference and other activities. The international convention center design is also expected to improve the quality and quantity of similar development for community place and improve the economy of Medan with regions and other countries. The design of North Sumatra Convention Center is expected to be able to support the big activities as mentioned above.